1956
DOI: 10.1111/j.1096-3642.1956.tb00482.x
|View full text |Cite
|
Sign up to set email alerts
|

MOULTING IN THE ANURA: THE NORMAL MOULTING CYCLE OF BUFO REGULARIS REUSS

Abstract: SUMMARY The normal behaviour pattern of Bufo regularis while moulting is described. The frequency of moulting has been determined in various conditions. At 20° C. these toads moult once every four to seven days. The frequency of moulting is not influenced by size, age or feeding, nor does there appear to be any difference in this regard between the sexes; any seasonal variation is slight. The frequency of moulting is greater at higher temperatures. Abrupt changes of temperature do not upset the moulting rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
4
13
0
Order By: Relevance
“…Sloughing in Rhinella marina was strongly affected by temperature with the intermoult interval of animals maintained at 10−20°C twice that of animals maintained at 20−30°C. These results are consistent with those of Taylor & Ewer (1956), who showed that in Bufo regularis maintained at 20°C, sloughing occurred half as frequently as in animals maintained at 30°C. Moreover, in B. regularis, sloughing frequency decreased even more dramatically at temperatures below 20°C, with animals at 15°C sloughing 4 times less frequently than animals maintained at 30°C.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Sloughing in Rhinella marina was strongly affected by temperature with the intermoult interval of animals maintained at 10−20°C twice that of animals maintained at 20−30°C. These results are consistent with those of Taylor & Ewer (1956), who showed that in Bufo regularis maintained at 20°C, sloughing occurred half as frequently as in animals maintained at 30°C. Moreover, in B. regularis, sloughing frequency decreased even more dramatically at temperatures below 20°C, with animals at 15°C sloughing 4 times less frequently than animals maintained at 30°C.…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of sloughing in regulating microbial abundance will depend to a large degree on the frequency of sloughing, which, as this and earlier studies (e.g. Taylor & Ewer 1956) show, is influenced by ambient temperature. Sloughing in Rhinella marina was strongly affected by temperature with the intermoult interval of animals maintained at 10−20°C twice that of animals maintained at 20−30°C.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Observed sloughing behaviour was consistent across individuals and aligns with previously published descriptions (Taylor & Ewer 1956;Larsen 1976; Despite this, the duration of sloughing (min, log-transformed) was not significantly longer in Table 2.2). This indicates that the stratum corneum of exposed frogs was no longer being sloughed in one piece, or the action of sloughing was less effective in exposed frogs.…”
Section: Sloughing Behavioursupporting
confidence: 87%